2002
DOI: 10.1073/pnas.212507099
|View full text |Cite
|
Sign up to set email alerts
|

Permanent and panerythroid correction of murine β thalassemia by multiple lentiviral integration in hematopoietic stem cells

Abstract: The viral titers produced were high enough to achieve transduction of virtually all of the hematopoietic stem cells in the graft with an average of three integrated proviral copies per genome in all transplanted mice; the transduction was sustained for >7 months in both primary and secondary transplants, at which time Ϸ95% of the red blood cells in all mice contained human ␤ globin contributing to 32 ؎ 4% of all ␤-like globin chains. Hematological parameters approached complete phenotypic correction, as assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
157
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(167 citation statements)
references
References 28 publications
4
157
0
6
Order By: Relevance
“…As a prerequisite to gene therapy clinical trials, it is essential that the efficacy and safety of candidate globin gene transfer vectors be tested in animal models of b-thalassaemia. Several studies to date have used murine models of relatively mild b-thalassaemia intermedia (May et al, 2000(May et al, , 2002Imren et al, 2002;Person et al, 2003;Hanawa et al, 2004), and have shown that b-globin gene transfer with lentivirus-based vectors can fully correct the thalassaemic phenotype in this animal model. The studies reported here demonstrated that c-globin gene transfer can fully correct the phenotype of murine b-thalassaemia intermedia, indicating that Hbb th)3 /+ mice represents a good model for testing candidate vectors for human c-globin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a prerequisite to gene therapy clinical trials, it is essential that the efficacy and safety of candidate globin gene transfer vectors be tested in animal models of b-thalassaemia. Several studies to date have used murine models of relatively mild b-thalassaemia intermedia (May et al, 2000(May et al, , 2002Imren et al, 2002;Person et al, 2003;Hanawa et al, 2004), and have shown that b-globin gene transfer with lentivirus-based vectors can fully correct the thalassaemic phenotype in this animal model. The studies reported here demonstrated that c-globin gene transfer can fully correct the phenotype of murine b-thalassaemia intermedia, indicating that Hbb th)3 /+ mice represents a good model for testing candidate vectors for human c-globin.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have focused on one of three murine models of relatively mild b-thalassaemia intermedia or sickle cell disease (May et al, 2000(May et al, , 2002Pawliuk et al, 2001;Imren et al, 2002;Person et al, 2003;Hanawa et al, 2004), while only one study has focused on a murine model of severe b-thalassaemia major (Rivella et al, 2003). Likewise, most of these studies have also focused on the use of recombinant virus vectors for wild type (WT) or variant forms of human b-globin (May et al, 2000(May et al, , 2002Pawliuk et al, 2001;Imren et al, 2002), while relatively few have focused on the use of vectors for human c-globin (Person et al, 2003;Hanawa et al, 2004). These and other studies (Person et al, 2001) have provided some information correlating the level of b-globin or c-globin gene expression with the level of phenotypic improvement in these models.…”
mentioning
confidence: 99%
“…These models have been used for numerous gene transfer studies to test the efficacy of lentiviruses containing various components of the human b-globin locus control region (LCR), promoter elements, and g-globin or b-globin gene constructs (May et al 2000(May et al , 2002Imren et al 2002;Nishino et al 2006;Han et al 2007;Lisowski and Sadelain 2007).…”
Section: Hemoglobinopathy Disease Models-in Vivo and In Vitromentioning
confidence: 99%
“…This indicates that TNS9 could generate 4 g/dL hemoglobin per vector copy in this in vivo setting, approximately half of hemizygous hemoglobin production (8.1±0.3 g/dL in Hbb th3/+ chimeras). Using the Hbb th1/th1 model of thalassemia, Imren et al 54 reported the pancellular permanent correction of the thalassemic phenotype with essentially the same cassette used in the successful gene therapy of a mouse model of sickle cell disease (SCD), except for the substitution of a normal in place of an antisickling ␤-globin gene. 54 Their vector boosted the hemoglobin production of 4.4 g/dL for an average of 3 vector copies per cell, an increase of 1.6 g/dL per VCN.…”
Section: -52mentioning
confidence: 99%